Effect of dichlorvos on growth of Scenedesmus acutus - Firat, Zehra; Cetin, A. Kadri (My University, 2009)
The effect of the dichlorvos on growth of the freshwater microalga Scenedesmus acutus was investigated. In general, the growth rate of S. acutus in control cultures are always high between 0 to 4 days, but that of cultures treated with dichlorvos were suddenly decreasing between 2 to 4 days. In contrast, in all control cultures the growth rate of S. acutus was always negative. These results demonstrated adverse effects of dichlorvos upon freshwater green algae (Scenedesmus acutus), thus, the application of this pesticide for control in agricultural practices must be done carefully since any disturbance affecting algae with similar or higher sensitivity will have severe repercussions on higher trophic levels.
Keywords: Algae; Dichlorvos; Growth rate; Scenedesmus acutus